EFFECTIVE MANAGEMENT STRATEGIES FUTSAL EXTRACURRICULAR PROGRAM AT SMK NEGERI 1 SOUTH BENGKULU - Oktafiani , Mutia; Danim, Sudarwan; Connie (UNIVERSITAS BENGKULU, 2024)
The aim of this research is to describe an effective strategy for the futsal extracurricular program at SMK Negeri 1 South Bengkulu. The type of research used in this research is qualitative research with a descriptive approach through field research. This method describes phenomena about what is experienced by research subjects, for example behavior, perceptions, motivation, actions, etc. holistically and with words and language in a natural context that utilizes various natural methods. The research results show that in this research there are four focuses that form conclusions. Effective strategies in managing futsal extracurriculars at SMK Negeri 1 South Bengkulu are: 1) Planning extracurricular futsal programs at SMK Negeri 1 South Bengkulu 2) implementing extracurricular futsal programs at SMK Negeri 1 South Bengkulu, 3) Evaluation of extracurricular futsal programs at SMK Negeri 1 Bengkulu South South by the school head is carried out periodically so that what is planned runs well and is in accordance with the school's vision and mission. 4), follow up on the results of the evaluation of the futsal extracurricular program at SMK Negeri 1 South Bengkulu.